2016
DOI: 10.1142/s2424835516500314
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Factors Affecting the Clinical Outcome of Septic Arthritis of the Shoulder

Abstract: Both arthroscopic and open surgery for septic shoulders showed satisfactory clinical outcomes. Old age and comorbidity were poor prognostic factors of clinical outcomes after treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 13 publications
1
14
0
Order By: Relevance
“…When we included data from studies [ 4 , 7 , 21 ] in which a mixed treatment approach was used, including open arthrotomy, our rate of reoperation of 5.6% was still low compared to reported rates ranging from 14.7% to 32%. We reviewed several studies that reported the reoperation rate for their case series ( Table 3 ).…”
Section: Discussionmentioning
confidence: 83%
See 3 more Smart Citations
“…When we included data from studies [ 4 , 7 , 21 ] in which a mixed treatment approach was used, including open arthrotomy, our rate of reoperation of 5.6% was still low compared to reported rates ranging from 14.7% to 32%. We reviewed several studies that reported the reoperation rate for their case series ( Table 3 ).…”
Section: Discussionmentioning
confidence: 83%
“…The authors noted a 26% rate of reoperation overall and a 25% rate of reoperation among cases treated with only the arthroscopic technique. Cho and Oh [ 7 ] reported a 14.7% rate of reoperation among 34 septic shoulders, with 22 treated by arthroscopy and 12 by an open approach; an 18.2% rate of reoperation was noted among cases treated with arthroscopy only. The open method was performed when there was evidence of osteomyelitis or abscess formation in the subcoracoid space on preoperative MRI.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Adhesive capsulitis, rotator cuff disease, and osteoarthritis are main causes of shoulder pain 12) . Although septic arthritis of the shoulder is a relatively rare disease, it has recently increased in prevalence due to an increase in life expectancy, various shoulder problem, local injection on shoulder region, and immunocompromised conditions 13) . The clinical manifestations of septic arthritis, such as shoulder pain with stiffness and fever, and elevated APR, can mimic PMR.…”
Section: Discussionmentioning
confidence: 99%